Great Indian Economists vol.10 Their creative vision for socio-economic development - Amartya Kumar Sen - Das, Debendra Kumar (ed) (New Delhi Deep & Deep Publications, 2004)
Professor Amartya Kumar Sen : life and sketch and economic philosophy